(untitled) (Anais do Salão Inovação, Ensino, Pesquisa e Extensão, 2020)
In this study, we detected Leishmania infantum infection in equines and evaluated hematological status. A total of 48 equines were selected between November and December 2016, from Uruguaiana, Rio Grande Do Sul, Brazil. All animals underwent general and dermatologic examinations and followed by blood samples collected to molecular diagnosis and hematological tests. Leishmania infantum was detected in two animals; the hematological analyses did not show statistical differences between the infected and non- infected groups. Although the infected horses showed slight alterations in the leukogram. The results may indicate that the equines were asymptomatic due to the absence of apparent clinical signs and the impossibility of relating hematological alterations between infected and non-infected groups.